2014
DOI: 10.1016/j.biochi.2013.07.009
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride-rich lipoproteins and cytosolic lipid droplets in enterocytes: Key players in intestinal physiology and metabolic disorders

Abstract: During the post-prandial phase, intestinal triglyceride-rich lipoproteins (TRL) i.e. chylomicrons are the main contributors to the serum lipid level, which is linked to coronary artery diseases. Hypertriglyceridemia can originate from decreased clearance or increased production of TRL. During lipid absorption, enterocytes produce and secrete chylomicrons and transiently store lipid droplets (LDs) in the cytosol. The dynamic fluctuation of triglycerides in cytosolic LDs suggests that they contribute to TRL prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 103 publications
2
67
0
1
Order By: Relevance
“…LDs present in the cytosol, which will be referred to as LD throughout this review) are observed in enterocytes of jejunum primarily if not only during lipid absorption (for review, see [3]). The minimal definition of a lipid droplet is a core of neutral lipids surrounded by a monolayer of amphipatic lipids and associated proteins.…”
Section: Physiological Functions Of Lipid Droplets In Enterocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…LDs present in the cytosol, which will be referred to as LD throughout this review) are observed in enterocytes of jejunum primarily if not only during lipid absorption (for review, see [3]). The minimal definition of a lipid droplet is a core of neutral lipids surrounded by a monolayer of amphipatic lipids and associated proteins.…”
Section: Physiological Functions Of Lipid Droplets In Enterocytesmentioning
confidence: 99%
“…A role of LDs in response to inflammatory stimuli in enterocytes is poorly documented but can be suspected due to links with production of prostaglandins, which are lipid mediators in inflammation [15]. Moreover, the favoured hydrophobic environment of LDs allows to store/metabolise hydrophobic molecules including lipophilic vitamins and xenobiotic compounds, which are abundant in the digested food present in the lumen of the jejunum (for review, see [3]). …”
mentioning
confidence: 99%
“…Alternatively, dietary lipids are stored in the cytosol as lipid droplets. 26,27 The cytosolic lipid droplets are subsequently mobilized and secreted during fasting state in enterocytes. Mobilization involves hydrolysis of triglycerides, mobilization of FFAs to the endoplasmic reticulum (ER), and resynthesis of triglycerides at the ER and subsequent secretion with lipoproteins.…”
Section: Distribution Of Trl Speciesmentioning
confidence: 99%
“…It is well known that intestinal enterocytes can transiently store dietary fatty acids after esterification into TAG in cytosolic lipid droplets [83,84]. In fact, a significant portion of absorbed fatty acids are first esterified into cytosolic lipid droplets as TAG, and then subsequently liberated by lipase action to be delivered into the endoplasmic reticulum where they are re-esterified and packaged onto nascent chylomicrons [85]. However, our understanding of the molecular mechanisms regulating intestinal TAG lipolysis and fatty acid re-esterification for packaging into nascent chylomicrons is still in its infancy.…”
Section: The Role Of Cgi-58 In the Intestinal Lipid Absorptionmentioning
confidence: 99%